Model Predictive Control for Hybrid Diesel-Electric Marine Propulsion *. Issue 1 (July 2017) - Papalambrou, Georgios; Samokhin, Sergey; Topaloglou, Sotirios; Planakis, Nikolaos; Kyrtatos, Nikolaos; Zenger, Kai
Abstract: In this work, the problem of energy management strategies in hybrid diesel-electric marine propulsion systems is investigated with the implementation of two types of Model Predictive Controllers. The system behavior is described by models based on system identification as well as on first-principles. These models were used for the design of linear and adaptive predictive controllers respectively. The controllers were successfully tested at HIPPO-1 testbed, at the Laboratory of Marine Engineering, evaluating diverse strategies for disturbance rejection, system stability, and operation of the plant within desirable limits.